Life-Cycle Management of Arabic Learning Programs in Pesantren - Putra, Muhammad Fatih Budiman; Ghufron, Boby; Akbar, Idrus Afandi (Journal of Arabic Language Studies and Teaching, 2024)
Dwi Pekan Bahasa, language program integrates Arabic and English environments, enhancing language skills through practical daily activities. This research focuses on delineating the life cycle management of the Dwi Pekan Bahasa program within Islamic boarding schools. Conducted at Darul Ukhuwah Islamic Boarding School (PPDU) in Malang, Indonesia, in 2023, the study employs a qualitative descriptive method and a case study approach, utilizing David Hopkins' theoretical framework for life cycle management. The investigation reveals a four-stage life cycle management process. The planning stage involves active participation of teachers, language coordinators, and supervisors to design a program responsive to student needs. Implementation encompasses diverse language activities and events. Evaluation includes weekly assessments for language coordinators and supervisors, along with daily evaluations for students in grades 1-4. The updating stage focuses on continuous improvement through the rotation of language coordinators and supervisors, improvements to instructional materials, and updates to language facilities.